In-vitro antioxidant activity of pet ether, methanolicandEthyl acetate extract of helicteres isora linn. - SUNNY SHARMA; SEEMA BHARGAVA (International Journal of Pharma and Bio Sciences, 2017)
The work is aimed to evaluate the antioxidant properties of three extracts (Pet Ether, Ethyl Acetate, and Methanolic) of Helicteres isora. In the present work antioxidant activity was determined by 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and Superoxide assay method and their IC50 values were calculated. Results showed that all the extracts of Helicteres isora shows significant free radicals inhibition. The methanolic extract shows maximum activity in both methods. DPPH radicals were inhibited at IC50 =35.61ug/ml with 68.76% antioxidant activity in methanolic extract while Superoxide (SOD) radicals were inhibition at IC50 =61.25 ug/ml with 61.23% antioxidant activity at 100ug/ml.The results suggest that three samples of Helicteres isorapossess almost similar antioxidant activity in comparison to standards and might be useful for further study of the Helicteres isora plant products and plant as whole for better drug and will help in prevention of chronic life style diseases which justifies the traditional use of this plant.